2012
DOI: 10.1016/j.jtcvs.2011.10.055
|View full text |Cite
|
Sign up to set email alerts
|

Robotic lobectomy for non–small cell lung cancer (NSCLC): Long-term oncologic results

Abstract: Robotic lobectomy for early-stage NSCLC can be performed with low morbidity and mortality. Long-term stage-specific survival is acceptable and consistent with prior results for VATS and thoracotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
176
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 256 publications
(192 citation statements)
references
References 18 publications
11
176
1
4
Order By: Relevance
“…The robotic approach involves articulated robotic arms together with a mini-thoracotomy. Large series of robotic lobectomy for early-stage lung cancer have now been reported and show excellent long-term oncological results [15,76]. Perioperative mortality is very low and complication rates similar to those expected with VATS lobectomy [15,76].…”
Section: Surgery For Early Stage Lung Cancer (Stage I and Ii)mentioning
confidence: 91%
See 3 more Smart Citations
“…The robotic approach involves articulated robotic arms together with a mini-thoracotomy. Large series of robotic lobectomy for early-stage lung cancer have now been reported and show excellent long-term oncological results [15,76]. Perioperative mortality is very low and complication rates similar to those expected with VATS lobectomy [15,76].…”
Section: Surgery For Early Stage Lung Cancer (Stage I and Ii)mentioning
confidence: 91%
“…Large series of robotic lobectomy for early-stage lung cancer have now been reported and show excellent long-term oncological results [15,76]. Perioperative mortality is very low and complication rates similar to those expected with VATS lobectomy [15,76]. PARK and FLORES [77] have reported that the cost of robotic lobectomy is still more than the cost of VATS lobectomy, but less than the cost of open lobectomy.…”
Section: Surgery For Early Stage Lung Cancer (Stage I and Ii)mentioning
confidence: 97%
See 2 more Smart Citations
“…Besides offering obvious technical advantages, such as 3D high-definition vision and dedicated endo-wristed instruments, there is increasing evidence that this technique is associated with reductions in mortality, length of hospital stay and overall complication rates when compared with both open and video-assisted thoracic surgery (VATS) [1]. Furthermore, in the setting of non-small-cell lung cancer, long-term oncological results have been shown to be at least equal to open surgery and VATS [2]. Nevertheless, with the introduction of this new technology, as already experienced in VATS, a shift in proceduralrelated problems and challenges can be expected.…”
Section: Introductionmentioning
confidence: 99%